Design of 9-D global chaotic system and its application in secure communication. Issue 1 (4th January 2021) - Liu, Meiting; Yu, Wenxin; Wang, Junnian; Chen, Yu; Bian, Yuyan
Abstract : Purpose: In this paper, a nine-dimensional chaotic system is designed and applied to secure communication. Design/methodology/approach: Firstly, the equilibrium characteristics, dissipativity, bifurcation diagram and Lyapunov exponent spectrum are used to analyze the relevant characteristics of the proposed nine-dimensional chaotic system. In the analysis of Lyapunov exponential spectrum, when changing the linear parameters, the system shows two states, hyperchaos and chaos. For secure communication, there is a large secret key space. Secondly, C0 complexity and SEcomplexity of the system are analyzed, which shows that the system has sequences closer to random sequences. Findings: The proposed nine-dimensional system has a large key space and more complex dynamic characteristics Originality/value: The results show that the proposed nine-dimensional hyperchaotic system has excellent encryption capabilities and can play an important role in the field of secure communication.